PENDAMPINGAN DALAM PENGEMBANGAN PENILAIAN AUTENTIK UNTUK MENINGKATKAN KINERJA GURU DI WILAYAH BINAAN TANGERANG - Riyan Arthur; Santoso Sri Handoyo; Daryati Daryati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
The purpose of this assistance is to provide a knowledge and practice basis for conducting authentic assessments and technical guidance in preparing and carrying out authentic assessments. Mentoring is done to improve the ability to conduct assessments, especially authentic assessments for teachers, so that teachers can understand and apply authentic assessments in the process of evaluating teaching and learning activities in schools. This place of assistance is at SMK Negeri 4 South Tangerang, the time of assistance on August 4 to Sept 1, 2018 the method used in the activities of the event include lectures, brainstorming, question and answer, workshops, assignments and live demonstrations. The mentoring results show that 80% the teacher of SMK Negeri 4 Tangerang understands the concept of authentic assessment as indicated by the work of the teacher in the form of test and non-test instruments which are reported to refer to authentic evaluation models of authentic evaluation rubrics. The results of this assistance were immediately reported to the principal and witnessed by the school supervisor as a facilitator